Sacrifice in Modernity Community, Ritual, Identity : From Nationalism and Nonviolence to Health Care and Harry Potter - Duyndam, Joachim; Korte, Anne-Marie (Brill, 2020)
Sacrifice seems to belong to a religious context of the past. In Sacrifice in Modernity: Community, Ritual, Identity it is demonstrated how sacrificial themes remain an essential element in our post-modern society. The shaping of community, performing rituals and the search for identity, three main characteristics of traditional sacrifice, are dynamics of our modern times as well which cannot be understood without sacrificial awareness. This is demonstrated in such areas as the German poet Hölderlin, Harry Potter, martyrdom, the Twilight Saga, the Japanese writer Endo, Tarkovsky, movies and more.